INDONESIAN-ENGLISH TRANSLATION SHIFTS FOUND IN THE SUBTITLE OF LASKAR PELANGI MOVIE - SAPUTRI, MUJIANI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: translation shift, subtitle, Laskar Pelangi.Translation is the way or a process to transform a language into another language to convey messages or information from the author but still keeping the original sense. Despite comprehending the language structure, the translator should understand the method and procedures of translator to avoid misunderstanding among the readers/audiences. One of translation procedures is shift, where it is a translation phenomenon that cannot be avoided by the translator in translation process. In this study, the researcher analyses translation shift which occurs in the English subtitle of Laskar Pelangi movie. There are two problems to be solved: (1) What are the types of translation shift found in the subtitle of Laskar Pelangi movie; (2) What are the possible reasons for the translator of Laskar Pelangi to do shifting.This study used qualitative approach in document analysis since it focused on  analyzing the Indonesian utterances which were produced by the characters of Laskar Pelangi movie. The data source was movie scripts where for the Indonesian script the researcher transcribed the movie by herself and the English version is in the form of subtitle downloaded from www.subscene.com. Then the data were analyzed by using theory proposed by Newmark (1988).From 275 Indonesian utterances, the researcher found 203 utterances which contain shift; and it consists of 57 utterances belong to type 1, 8 utterances belong to type 2, 30 utterances belong to type 3, and 108 utterances belong to type 4. Then from the analysis, the researcher found several possible reasons for the translator to do shifting. The result showed that mostly, shift occurred because of the differences of grammar.The researcher suggests the next researchers to use another theory in order to enrich the various result of translation research. It is suggested to the next researchers to investigate other objects, such as novel, song lyric, bilingual story book, and many other media.